DIGITALISING HALAL CERTIFICATION: The Dynamic of Regulations and Policies Concerning Halal Certification in Indonesia - Santoso, Lukman; Rachman, Abdul (Jurisdictie: Jurnal Hukum dan Syariah, 2023)
The global halal product market is proliferating, fuelling increased demand for quality halal products. To fulfil halal certification requirements, Micro, Small and Medium Enterprises (MSMEs) in East Java Province, Indonesia face challenges in the certification process which is manual, time-consuming and inefficient. To overcome these problems, this study aims to explore the urgency of digitalising halal certification for optimal impact on improving the quality of halal products for MSMEs in East Java. This research employed a qualitative method with a literature and conceptual juridical approach. This research used primary and secondary data, namely BPJPH data, the Office of Cooperatives and SMEs of East Java Province. The results of this study indicate that government regulations and policies related to halal certification provide legal certainty for digital transformation in the implementation of halal certification in East Java Province. Although the achievements of MSMEs in East Java Province are low compared to those of other provinces, the digitalisation of halal certification can effectively help the MSMEs in East Java Province to reduce costs, expedite halal certification processing time, and increase compliance with halal requirements so that acceleration and increase in the number of halal certifications for MSMEs can take place properly. Pasar produk halal global terus berkembang dengan pesat dan mendorong peningkatan permintaan terhadap produk halal yang berkualitas. Untuk memenuhi persyaratan sertifikasi halal, Usaha Mikro, Kecil, dan Menengah (UMKM) di Provinsi Jawa Timur, Indonesia menghadapi tantangan dalam proses sertifikasi yang manual, memakan waktu, dan kurang efisien. Untuk mengatasi masalah tersebut, penelitian ini bertujuan mengeksplorasi urgensi digitalisasi sertifikasi halal sehingga berdampak optimal terhadap peningkatan kualitas produk halal UMKM di Jawa Timur. Metode penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan netnografi dan yuridis konseptual. Penelitian ini menggunakan data hasil wawancara dengan pegiat sertifikasi halal dan data dari situs BPJPH, Dinas Koperasi dan UKM Provinsi Jawa Timur. Hasil penelitian ini menunjukkan bahwa regulasi dan kebijakan pemerintah terkait sertifikasi halal memberikan kepastian hukum terhadap transformasi digital dalam pelaksanaan sertifikasi halal di Provinsi Jawa Timur. Walaupun capaian pelaku UMKM di Provinsi Jawa Timur tergolong rendah dibandingkan dengan provinsi lainnya, namun digitalisasi sertifikasi halal efektif dapat membantu UMKM Provinsi Jawa Timur untuk mengurangi biaya, mempercepat waktu sertifikasi halal, dan meningkatkan kepatuhan terhadap persyaratan halal sehingga percepatan dan peningkatan jumlah sertifikasi halal bagi UMKM dapat terlaksana dengan baik.